MIXED-ENGLISH PROFICIENCY CLASS: A REVIEW ON ISSUES AND STRATEGIES - Sri Gustiani (Politeknik Negeri Sriwijaya, 2018)
The purpose of this paper is to illuminate some issues regarding mixed-English proficiency classes for English Language Teaching in the context of Teaching English as a Foreign Language. The existing literatures reveals that there are pros and contras of this class in the forms of ways in grouping the students which lead to students’ different learning styles and interest, and teachers’ teaching and learning materials and methodology. Indeed, this English heterogeneous type of class brings potential risks for the students’ achievement. This paper also proposes three most common Differentiated Instruction strategies to engage mixed-English students in EFL teaching and learning processes more effectively.